Способ прогнозирования изностойкости твердосплавных режущих инструментов - Нестеренко В. П. Владимир Петрович; Тюрин Ю. И. Юрий Иванович; Минакова Т. С.; Николаева В. П.; Арефьев К. П. Константин Петрович
опубл. 27.08.09